National centralized drug procurement and health care expenditure of households—micro-evidence from CFPS - Li, Xin; Tao, Ran; Jin, Yuning; Li, Na (Frontiers in Public Health, 2024)
[Abstract] This paper utilizes data from the China Family Panel Studies (CFPS) to evaluate the impact of the “4+7” National Centralized Drug Procurement (NCDP) on Per Capita Household Health Care Expenditure (PCHHCE) through the application of Differences-in-Differences (DID) methodology. Research indicates that the implementation of NCDP led to a reduction of 10.6% in PCHHCE. Despite conducting various tests like the Permutation test, Propensity Score Matching, alterations in regression methodologies, and considering individual fixed effects, the results remained consistent. Additionally, the research identifies diversity in NCDP effects among various household characteristics. Particularly, the impact is more significant for households residing in rural regions of China, enrolled in Basic Medical Insurance for urban & rural residents and urban workers, and having an income bracket of 25%-75%. These findings carry policy implications for the future expansion and advancement of NCDP in China.